2022
DOI: 10.34312/euler.v10i2.16708
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Regresi Robust Estimasi Least Trimmed Square dan Estimasi Maximum Likelihood pada Pemodelan IPM di Pulau Sulawesi

Abstract: Sulawesi Island is one of the islands in Indonesia with the second lowest HDI after Papua in 2011-2018, so it is necessary to study more deeply the factors that affect the HDI on Sulawesi Island. One of the methods in modeling is the robust regression method that can be used even though there are outliers in the data. This study aimed to determine the factors that affect HDI in Sulawesi Island using a robust regression model of Least Trimmed Square (LTS) estimation and Maximum Likelihood (M) estimation and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Giving this weight makes the estimate quite resistant to outliers so that it does not have a significant impact on the resulting estimator. There are several estimation methods in robust regression, namely the Scale (S) estimator, Maximum Likelihood (M) estimator, Method of Moment (MM) estimator, Least Median of Square (LMS) Estimator, and Least Trimmed of Square (LTS) Estimator (Akolo & Nadjamuddin, 2022) Therefore, based on the above two explanations, it can be concluded that the coefficient of determination (R 2 ) test indicates the ability of all independent variables to jointly explain the diversity of the dependent variable. If the value of R 2 is equal to 0, we know that the independent variable cannot explain the variation in the dependent variable.…”
Section: Operationalization Of Research Variablesmentioning
confidence: 99%
“…Giving this weight makes the estimate quite resistant to outliers so that it does not have a significant impact on the resulting estimator. There are several estimation methods in robust regression, namely the Scale (S) estimator, Maximum Likelihood (M) estimator, Method of Moment (MM) estimator, Least Median of Square (LMS) Estimator, and Least Trimmed of Square (LTS) Estimator (Akolo & Nadjamuddin, 2022) Therefore, based on the above two explanations, it can be concluded that the coefficient of determination (R 2 ) test indicates the ability of all independent variables to jointly explain the diversity of the dependent variable. If the value of R 2 is equal to 0, we know that the independent variable cannot explain the variation in the dependent variable.…”
Section: Operationalization Of Research Variablesmentioning
confidence: 99%